Hubungan Pola Asuh Demokratis Dengan Perkembangan Bahasa Pada Anak Prasekolah Di TK Negeri Tabanan Di Kerambitan - Ni Made Ari Sukmandari (STIKES ADVAITA MEDIKA TABANAN, 2020)
During preschool children experience the development of language skills very quickly which becomes the foundation for subsequent development. Language development is influenced by various factors including the parenting democratic parent. This study aimed at determine democratic parenting to the language development of preschool children in Tabanan Kindergarten Kerambitan. This study was a descriptive correlational research with cross sectional approach. Democratic parenting was measured using the parenting questionnaire and language development with the Denver Developmental Screening Test II. Respondents analyzed were kindergarten students in Tabanan Kerambitan taken with total sampling techniques. The results obtained that parenting was quite democratic as many as 32 people (64%) and language development was mostly included in the normal category (96.0%) The results of the correlation test with the Spearman Rho test showed p = 0.018 and r = 0.332. This meant that there was a significant correlation between parenting with language development and had a fairly strong positive correlation. It is recommended to increase understanding of democratic parenting and language development in children, make innovative efforts in applying democratic parenting according to child development, environmental influences and technological development